The Effect of Barrier and Knee Tuck Jump Exercises on Volleyball's Vertical Jump Smash Ability - Agustan, Boby; Nuryasin, Alif (Physical Activity Journal (PAJU), 2024)
This study examines the effect of barrier jump and knee tuck jump exercises on volleyball's vertical jump smash ability. This study was accomplished for volleyball extracurricular students at SMP Negeri 3 Kuningan. The research method is an experiment with a one-group pre-test and post-test design. The number of samples in this study was 14 students. The data collection technique acquired tests and measurements of barrier and knee tuck jumps on Vertical Jump Smash abilities. This research reveals that structured jump training can significantly enhance vertical jump performance in junior high school students engaged in volleyball. The results indicate a statistically significant difference between the pre-test and post-test scores, suggesting that the training program had a meaningful impact on the participants ' jumping abilities. The effectiveness of the applied training methods contributes to the broader understanding of athletic performance enhancement in youth sports programs